Histopathological spectrum of benign melanocytic nevi - our experience in a tertiary care centre - Shivanand Gundalli; Smita Kadadavar; Somil Singhania; Rutuja Kolekar (Our Dermatology Online, 2016)
Introduction: Melanocytic lesions show great morphological diversity in their architecture and the cytomorphological appearance of their composite cells. Histological assessment of these melanocytic nevi constitutes a substantial proportion of a dermatopathologist's daily workload. The aim of our study was to observe the histological spectrum and types of benign melanocytic nevi and melanoma and also to identify the unusal/atypical histological features in these melanocytic nevi. Results: Intradermal nevus was the most common benign melanocytic nevi comprising 11 (62.5%) out of the total 13 cases. In ten cases lesions were located on head and neck region. Maximum number (60%) of cases were seen between 30-40 years of age. Conclusion: Melanocytic lesions of the skin are of notorious challengefor the pathologist. Face was the most common site and intradermal nevus was the most common lesion in our study.